2022
DOI: 10.1080/10286632.2021.2022653
|View full text |Cite
|
Sign up to set email alerts
|

Scandinavian success as European policy dilemma: creative Europe’s funding for TV drama co-productions, 2014-20

Abstract: Scandinavian success as European policy dilemma Creative Europe's funding for TV drama co-productions, 2014-20This article surveys the fiction productions that received funding from Creative Europe's TV Programming scheme 2014-2020. The evaluation shows that most funding went to North-Western Europe with Scandinavia surpassing Europe's big TV producing nations. The geographical and genre imbalances in the TV scheme must be seen in the light of the long-established close collaboration between Germany and primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…16 Nordvision has even been credited as one factor behind the recent international success of Scandinavian drama series: research on the European Commission's support for television fiction between 2014 and 2020 found that Scandinavian countries were exceptionally successful in obtaining funding, which researchers saw as a result of the decades long institutionalization of co-production relationships within Nordvision. 17 My aim in this article is not, however, to evaluate Nordvision in terms of success or failure, but to describe some of the work that has gone into building this network of Nordic television organizations.…”
mentioning
confidence: 99%
“…16 Nordvision has even been credited as one factor behind the recent international success of Scandinavian drama series: research on the European Commission's support for television fiction between 2014 and 2020 found that Scandinavian countries were exceptionally successful in obtaining funding, which researchers saw as a result of the decades long institutionalization of co-production relationships within Nordvision. 17 My aim in this article is not, however, to evaluate Nordvision in terms of success or failure, but to describe some of the work that has gone into building this network of Nordic television organizations.…”
mentioning
confidence: 99%